Nitrogen Supply Affects Photosynthesis and Photoprotective Attributes During Drought-Induced Senescence in Quinoa - Bascuñán-Godoy, Luisa; Sanhueza, Carolina; Hernández, Cristián E.; Cifuentes, Leonardo; Pinto, Katherine; Álvarez, Rodrigo; González-Teuber, Marcia; Bravo, León A. (Frontiers in Plant Science, 2018)
Drought during senescence has become more common in Mediterranean climates in recent years. Chenopodium quinoa Willd has been identified as tolerant to poor soil conditions and drought. Previous observations have found that sufficient nitrogen (N) supply mitigates yield losses under terminal drought conditions. However, there is no understanding of the mechanisms behind this effect. We hypothesized that N up-regulates both photosynthetic and photoprotective elements during drought-induced senescence, alleviating the negative impact of drought on yield. The role of N supply and terminal-drought on photoprotection was tested using three Chilean quinoa genotypes from different climatic zones: Faro, UdeC9 and BO78. Plants were grown under high nitrogen (HN) or low nitrogen (LN) conditions and subjected to terminal drought at the onset of senescence. Photosynthetic and photochemical and non-photochemical processes were evaluated at both the onset of drought and after 15 days of drought conditions. N supplementation modified most of the physiological parameters related to photochemical dissipation of energy, photosynthesis and yield in quinoa. In contrast, water restriction did not affect photosynthesis in quinoa, and its effect on yield was dependent on the genotype. A significant interaction NxG was observed in photosynthesis, relative water content, protein content, Fv/Fm and chlorophylls. In general, Faro was able to maintain higher the levels of these attributes under LN conditions than UdeC9 and BO78.In addition, interacting effects of NxW regulated the level of most pigments in quinoa as well as the photoprotective induction of non-photochemical quenching (NPQ) during senescence. During terminal-drought at LN conditions, Faro presented a larger NPQ induction under drought conditions than UdeC9 and BO78, which was supported by a larger zeaxanthin content and de-epoxidation state of xanthophyll pool. Interestingly, BO78 did not induce NPQ in response to drought-induced senescence but instead enhanced the content of betacyanins. This response needs to be researched in future works. Finally, we observed that LN supply reduced the correlationship among the de-epoxidation state of xanthophyll cycle and NPQ. This could be indicating that N supply not only compromised the capacity for photosynthetic performance in quinoa plants, instead also affected the plasticity of thermal dissipation, restricting further changes during drought-induced-senescence.